Antirust coating composition as well as preparation method and application thereof
The high-temperature protective coating constructed with components such as BiVO4 composite materials and modified resins solves the problem of insufficient heat resistance and corrosion resistance of traditional coatings in high-temperature environments, and realizes the dynamic self-healing and efficient protection effect of the coating.
Patent Information
- Application Number
- CN202511213467.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-28
- Publication Date
- 2025-10-03
- Estimated Expiration
- 2045-08-28
AI Technical Summary
Traditional coatings lack heat resistance, crack resistance and adhesion in high-temperature environments and cannot effectively prevent corrosion, resulting in degraded equipment performance and safety hazards.
BiVO4 composite materials, chlorophosphazene polymers, glass ceramics and other multifunctional components are prepared by hydrothermal method. The BiVO4 composite materials are combined with modified resins and phosphate coupling agents to form high-temperature protective coatings. The adaptive deformation and self-healing ability of oxygen vacancies, zirconium phosphate layered structures and phosphate groups are utilized to construct a dynamic stress buffer network, thereby enhancing the thermal stability and corrosion resistance of the coating.
It effectively inhibits electrochemical corrosion in high temperature environments, buffers thermal stress, realizes the dynamic self-healing ability of the coating, and improves the protective performance and service life of the coating.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of anti-rust coatings and relates to an anti-rust coating composition and a preparation method and application thereof. Background Art
[0002] With the rapid development of industrialization, high-temperature transportation pipelines have been widely used in petrochemical, natural gas transportation, and energy equipment. However, under the long-term influence of high temperature, high pressure, and corrosive media, pipeline surfaces are highly susceptible to corrosion due to the harsh environment, resulting in reduced equipment performance, shortened service life, and even serious safety hazards. Especially under extreme temperature conditions, the anti-corrosion coating on pipeline surfaces is often at risk of failure. High temperatures can cause thermal expansion and contraction of the coating, leading to the accumulation of thermal stress, which can cause cracking, delamination, or flaking of the coating. This not only accelerates the corrosion process of the substrate but also further threatens the safety and stability of the facility.
[0003] Traditional coating systems primarily rely on single organic resins or inorganic fillers, but these materials have significant limitations in heat resistance, crack resistance, and adhesion, making them unable to meet the long-term use requirements of high-temperature transportation pipelines. Furthermore, chemically corrosive media at extreme temperatures can further damage the interface between the coating and the substrate, significantly reducing the coating's protective properties. Therefore, developing an anti-corrosion coating material that can maintain long-term stability in high-temperature environments, exhibit excellent corrosion protection, and possess good mechanical properties is of great practical significance for the reliable operation and extended service life of high-temperature industrial equipment. Summary of the Invention
[0004] In response to the shortcomings of the prior art, the present invention aims to provide an anti-rust coating composition, its preparation method, and application. By introducing multifunctional components such as BiVO4 composite materials, chlorophosphazene polymer composites, and glass ceramics, the present invention constructs a coating system with excellent thermal stability, mechanical strength, and corrosion resistance. The BiVO4 composite material is prepared by a hydrothermal method and has oxygen vacancies and good thermal stress regulation capabilities; the chlorophosphazene polymer composite provides chemical corrosion resistance and thermal stability; and the glass ceramics enhance the coating's crack resistance and high-temperature resistance through high-temperature melting and ammonia treatment. The above-mentioned multiple components are dispersed and uniformly mixed through a modified resin and a phosphate coupling agent to form a high-temperature protective coating, thereby meeting the needs of actual production.
[0005] To achieve this object, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a method for preparing an anti-rust coating composition, the preparation method comprising: A1, dispersing bismuth nitrate pentahydrate in a nitric acid solution to obtain a bismuth solution, dispersing ammonium metavanadate in a sodium hydroxide solution and adding the solution to the bismuth solution for a hydrothermal reaction to obtain BiVO4, placing the BiVO4 in a tube furnace and introducing a mixed gas to maintain the temperature to obtain BiVO4-δ, mixing α-zirconium phosphate and BiVO4-δ, ball-milling the mixture, immersing the mixture in a sodium dihydrogen phosphate solution, filtering, washing, and drying to obtain a BiVO4 composite material; S1, dispersing 4,4'-difluorobenzophenone and 4,4'-biphenol in sulfolane and adding potassium carbonate to react, adding pentafluorophenyltriethoxysilane to continue the reaction to obtain a modified resin, and dispersing the modified resin in N-methylpyrrolidone to obtain a resin solution; S2, dispersing the BiVO4 composite material, the chlorophosphazene polymer composite, the glass ceramic and the phosphate coupling agent in N-methylpyrrolidone, adding the resin solution after ultrasonic dispersion, and obtaining an anti-rust coating composition.
[0006] Specifically include: A1, dispersing bismuth nitrate pentahydrate in a nitric acid solution to obtain a bismuth solution, dispersing ammonium metavanadate in a sodium hydroxide solution and adding the solution to the bismuth solution, adjusting the pH to 2.0-2.5, transferring the solution to a polytetrafluoroethylene-lined reactor for a hydrothermal reaction, and drying the solution to obtain BiVO4, placing the BiVO4 in a tube furnace, introducing a mixed gas, heating the solution to a first temperature and maintaining the temperature to obtain BiVO4-δ, mixing α-zirconium phosphate with the BiVO4-δ, ball-milling the mixture, immersing the mixture in a sodium dihydrogen phosphate solution, and filtering, washing, and drying the mixture to obtain a BiVO4 composite material; A2, dispersing silicotungstic acid in anhydrous ethanol to obtain a silicotungstic acid ethanol solution, dispersing the chlorophosphazene polymer in anhydrous ethanol and adding the silicotungstic acid ethanol solution to the mixture, stirring evenly, filtering, washing, and drying to obtain a chlorophosphazene polymer composite; A3, mixing aluminum dihydrogen phosphate, basic magnesium carbonate, and lithium molybdate, ball-milling the mixture, adding ammonium dihydrogen phosphate, and allowing to stand and mature to obtain a mixture, heating the mixture to a second temperature and maintaining the temperature to obtain a melt, pouring the melt into ice water, immersing the fragments in ammonia water, and ball-milling and drying to obtain a glass ceramic; S1, dispersing 4,4'-difluorobenzophenone and 4,4'-biphenol in sulfolane and adding potassium carbonate, under a nitrogen atmosphere, heating to a third temperature for reaction, cooling to a fourth temperature and adding pentafluorophenyltriethoxysilane to continue the reaction, cooling the reaction solution to room temperature and pouring into ice water to obtain a precipitate, crushing the precipitate, washing and drying to obtain a modified resin, and dispersing the modified resin in N-methylpyrrolidone to obtain a resin solution; S2, dispersing the BiVO4 composite material, the chlorophosphazene polymer composite, the glass ceramic and the phosphate coupling agent in N-methylpyrrolidone, adding the resin solution after ultrasonic dispersion, and grinding with a three-roll mill to obtain an anti-rust coating composition.
[0007] In high-temperature pipeline service environments, the metal matrix is extremely susceptible to passivation film rupture and stress corrosion cracking. Bismuth vanadate, after reduction treatment, introduces high-concentration oxygen vacancy defects. These defects become deep capture centers for free electrons at high temperatures. When the pipeline metal undergoes anodic dissolution reaction, oxygen vacancies continuously capture conduction electrons, inhibiting the kinetics of the cathode oxygen reduction reaction, fundamentally weakening the efficiency of the electrochemical corrosion cell. The layered crystal structure of zirconium phosphate has unique asymmetric thermal expansion characteristics, and its interlayer slip ability can effectively buffer the shear stress caused by the difference in thermal expansion coefficients between the coating and the carbon steel substrate. This micro- and nano-scale adaptive deformation behavior converts macroscopic thermal stress into energy dissipation at the lattice level, significantly reducing the probability of microcrack initiation in the coating during temperature cycling. Crucially, the active phosphate groups enriched on the zirconium phosphate surface migrate directionally toward coating defects driven by high temperatures, reacting with exposed iron ions to form a dense iron phosphate network, instantly sealing the entrances to the corrosion channels. Simultaneously, vanadium oxides released by the decomposition of bismuth vanadate contribute to the construction of a composite passivation layer with a spinel topology. Its three-dimensional ion channels effectively block oxygen ion diffusion, enabling dynamic self-reinforcement of the passivation film at extreme temperatures. Simultaneously, dihydrogen phosphate ions react with hydroxyl groups on the zirconium phosphate surface to form stable covalent bonds, transforming the inert layered material into an active phosphate-rich platform. Second, phosphate groups act as molecular bridges connecting the interfaces of bismuth vanadate and zirconium phosphate, forming a high-strength heterojunction via double-ended coordination bonds and inhibiting high-temperature phase separation. Finally, the surface-loaded phosphates serve as a self-repair source during pipeline service. When microcracks appear in the coating or the substrate is exposed, the active phosphorus species generated by the phosphate pyrolysis rapidly react with iron ions to form a dense iron phosphate passivation film, instantly sealing the corrosion channels.
[0008] Phosphazene chloride polymer is a polymer compound containing phosphorus and nitrogen bonds, with excellent heat resistance and chemical stability within its molecular backbone. The polymetallic oxygen clusters of silicotungstic acid cross-link with the polymer side chains through strong ionic bonds, forming a nanoscale interpenetrating network structure. This effectively prevents microcrack nucleation when local stress concentrations occur in pipeline systems due to sudden temperature changes or pressure shocks. Silicotungstic acid undergoes progressive hydrolysis in high-temperature and high-humidity environments. The released tungsten oxide anions diffuse along the concentration gradient to the damaged area of the coating, where they react with the ferrous ions produced by electrochemical dissolution to form ferric tungstate polymers. This precipitate preferentially deposits at the microcrack tips and within the pores, achieving physical closure of the damaged area through volume expansion. Its semiconductor properties also inhibit the development of localized galvanic corrosion. Furthermore, the polymer backbone of the phosphazene chloride polymer effectively buffers thermal stresses in the coating system, reducing cracking caused by thermal expansion mismatch.
[0009] Penetration and erosion by molten salt media at high temperatures and weakening of the coating / substrate interface are the primary causes of pipeline failure. The phosphate glass network undergoes controlled phase separation during the thermal history, forming a connected amorphous phase that serves as a high-speed channel for ion migration. Lithium ions, with their smallest ionic radius and highest mobility, preferentially diffuse to the coating surface and combine with aggressive anions in the molten salt to form stable compounds. Simultaneously, molybdate ions chemically adsorb on the metal substrate, forming a negatively charged barrier that repels aggressive media such as chloride ions and establishes a selective permeability barrier within the coating. Rapid cooling of the melt in ice water rapidly forms a glassy material. This process inhibits excessive crystalline growth, resulting in a highly uniform microstructure. The fragments are then post-treated in ammonia water. The alkalinity of the ammonia modifies the surface of the material, imparting enhanced interfacial bonding properties. This post-treatment not only neutralizes residual acidic components but also forms an ammonium salt buffer layer at the interface. This layer stabilizes the chemical environment in the transition zone through a hydrogen bonding network, inhibiting adhesion degradation caused by interfacial hydrolysis.
[0010] Traditional polymers suffer from segmental dissociation and weakened interfacial bonding at high temperatures, leading to coating failure. The spatial conjugation effect of the biphenyl structure significantly enhances molecular chain rigidity, and the torsional barrier between its two benzene rings effectively hinders molecular chain slip and free radical chain scission reactions at high temperatures. Fluorosilane endcapping agents undergo a step-by-step reaction during the curing process: the siloxane group first hydrolyzes to form a highly reactive silanol, which then dehydrates and condenses with the hydroxyl groups on the metal surface to form a covalent bond between siloxane and iron; the perfluorophenyl group then forms a high-strength electrostatic adsorption layer on the substrate surface through a strong electron-withdrawing effect. This synergistic effect of covalent bonding and physical adsorption enhances interfacial binding energy. Furthermore, the ether bonds in the resin molecular chain impart moderate flexibility, allowing for microelastic deformation under thermal stress, thus preventing peeling failure caused by interfacial stress concentration. In the final protective system constructed by the coating, the interlayer slip of zirconium phosphate and the molecular chain movement of phosphazene polymer form a dynamic stress buffer network. The glass-ceramic particles act as rigid fillers to block the propagation path of microcracks. The compressive stress field generated by the gradient of its thermal expansion coefficient makes the cracks tend to close. At the moment the microcracks are generated, the molten phase on the surface of the glass-ceramic particles flows into the cracks under capillary action to achieve physical filling. At the same time, the tungsten oxide anions dissociated from silicotungstic acid react with metal ions at the crack tip to form a closed precipitate; the phosphate released by zirconium phosphate forms a chemical passivation film with the matrix metal, the oxygen vacancies of bismuth vanadate selectively adsorb sulfate ions, the lithium ion trap of the glass-ceramic captures chloride ions, and the dense aromatic ring structure of the biphenyl resin constructs a molecular-level screening barrier to block the diffusion path of small molecule corrosive media to the substrate interface.
[0011] As a preferred technical solution of the present invention, in A1, the mass ratio of bismuth nitrate pentahydrate to ammonium metavanadate is (4.8-5.0): (1.1-1.2), for example, it can be (4.80, 4.82, 4.84, 4.86, 4.88, 4.90, 4.92, 4.94, 4.96, 4.98 or 5.00): (1.10, 1.11, 1.12, 1.13, 1.14, 1.15, 1.16, 1.17, 1.18, 1.19 or 1.20), but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0012] In some optional examples, the mass ratio of the bismuth nitrate pentahydrate to the nitric acid solution is (4.80, 4.82, 4.84, 4.86, 4.88, 4.90, 4.92, 4.94, 4.96, 4.98 or 5.00):30, for example, it can be (4.8-5.0):30, and the concentration of the nitric acid solution is 4M, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0013] In some optional examples, the mass ratio of the ammonium metavanadate to the sodium hydroxide solution is (1.1-1.2):25, for example, it can be (1.10, 1.11, 1.12, 1.13, 1.14, 1.15, 1.16, 1.17, 1.18, 1.19 or 1.20):25, and the concentration of the sodium hydroxide solution is 2M, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0014] In some optional examples, the temperature of the hydrothermal reaction is 180-185°C, for example, it can be 180.0°C, 180.5°C, 181.0°C, 181.5°C, 182.0°C, 182.5°C, 183.0°C, 183.5°C, 184.0°C, 184.5°C or 185.0°C, and the time of the hydrothermal reaction is 12-13h, for example, it can be 12.0h, 12.1h, 12.2h, 12.3h, 12.4h, 12.5h, 12.6h, 12.7h, 12.8h, 12.9h or 13.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0015] In some optional examples, the mixed gas is a H2 / Ar mixed gas, the volume fraction of hydrogen is 5%, and the total flow rate is 50 mL / min.
[0016] In some optional examples, the first temperature is 400-420°C, for example, it can be 400°C, 402°C, 404°C, 406°C, 408°C, 410°C, 412°C, 414°C, 416°C, 418°C or 420°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0017] In some optional embodiments, the first temperature insulation time is 2-3h, for example, it can be 2h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9 or 3.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] In some optional examples, the mass ratio of the α-zirconium phosphate to BiVO4-δ is 1:1.
[0019] In some optional examples, the concentration of the sodium dihydrogen phosphate solution is 0.1M.
[0020] As a preferred technical solution of the present invention, in A2, the mass volume ratio of silicotungstic acid to anhydrous ethanol in dispersing silicotungstic acid is (10-10.5) g:50 mL, for example, it can be (10, 10.05, 10.1, 10.15, 10.2, 10.25, 10.3, 10.35, 10.4, 10.45 or 10.5) g:50 mL, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0021] In some optional examples, the mass volume ratio of the chlorinated phosphazene polymer to the anhydrous ethanol is 1 g:10 mL when the chlorinated phosphazene polymer is dispersed in the anhydrous ethanol.
[0022] In some optional examples, the mass ratio of the silicotungstic acid to the chlorophosphazene polymer is (2-2.1):1, for example, it can be (2.00, 2.01, 2.02, 2.03, 2.04, 2.05, 2.06, 2.07, 2.08, 2.09 or 2.10):1, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0023] As a preferred technical solution of the present invention, in A3, the mass ratio of the aluminum dihydrogen phosphate, basic magnesium carbonate, lithium molybdate and ammonium dihydrogen phosphate is (50-55): (30-35): 15: (8-10), for example, it can be (50.0, 50.5, 51.0, 51.5, 52.0, 52.5, 53.0, 53.5, 54.0, 54.5 or 55.0): (30.0, 30.5, 31.0, 31.5, 32.0, 32.5, 33.0, 33.5, 34.0, 34.5 or 35.0): 15: (8.0, 8.2, 8.4, 8.6, 8.8, 9.0, 9.2, 9.4, 9.6, 9.8 or 10.0), but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0024] In some optional examples, the static aging time is 12-13 hours, for example, it can be 12.0 hours, 12.1 hours, 12.2 hours, 12.3 hours, 12.4 hours, 12.5 hours, 12.6 hours, 12.7 hours, 12.8 hours, 12.9 hours or 13.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] In some optional examples, the second temperature is 1300-1320°C, for example, it can be 1300°C, 1302°C, 1304°C, 1306°C, 1308°C, 1310°C, 1312°C, 1314°C, 1316°C, 1318°C or 1320°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0026] In some optional examples, the second temperature holding time is 1.5-2.0h, for example, 1.5h, 1.55h, 1.6h, 1.65h, 1.7h, 1.75h, 1.8h, 1.85h, 1.9h, 1.95h or 2.0h, but is not limited to the enumerated values, and other unenumerated values within the numerical range are also applicable. In some optional examples, the mass fraction of the ammonia solution is 5wt.%.
[0027] As a preferred technical solution of the present invention, in S1, the mass ratio of the 4,4'-difluorobenzophenone, 4,4'-biphenol, sulfolane, potassium carbonate and pentafluorophenyltriethoxysilane is (100-115): (60-65): 600:70:5, for example, it can be (100.0, 101.5, 103.0, 104.5, 106.0, 107.5, 109.0, 110.5, 112.0, 113.5 or 115.0): (60.0, 60.5, 61.0, 61.5, 62.0, 62.5, 63.0, 63.5, 64.0, 64.5 or 65.0): 600:70:5, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0028] In some optional examples, the third temperature is 190-195°C, for example, it can be 190.0°C, 190.5°C, 191.0°C, 191.5°C, 192.0°C, 192.5°C, 193.0°C, 193.5°C, 194.0°C, 194.5°C or 195.0°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] In some optional examples, the time of the third temperature reaction is 3-4h, for example, it can be 3.0h, 3.1h, 3.2h, 3.3h, 3.4h, 3.5h, 3.6h, 3.7h, 3.8h, 3.9h or 4.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0030] In some optional examples, the fourth temperature is 150-155°C, for example, it can be 150.0°C, 150.5°C, 151.0°C, 151.5°C, 152.0°C, 152.5°C, 153.0°C, 153.5°C, 154.0°C, 154.5°C or 155.0°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] In some optional examples, the continued reaction time is 2-3h, for example, it can be 2.0h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h or 3.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] As a preferred technical solution of the present invention, in S2, the mass ratio of the BiVO4 composite material, the chlorophosphazene polymer composite, the glass ceramic, the phosphate coupling agent, the N-methylpyrrolidone and the resin solution is (8-10): (5-7): (10-13): 1:20: (65-70), for example, it can be (8.0, 8.2, 8.4, 8.6, 8.8, 9.0, 9.2, 9.4, 9.6, 9.8 or 10.0): (5.0, 5.2, 5.4, 5.6, 5. 8, 6.0, 6.2, 6.4, 6.6, 6.8 or 7.0): (10.0, 10.3, 10.6, 10.9, 11.2, 11.5, 11.8, 12.1, 12.4, 12.7 or 13.0): 1: 20: (65.0, 65.5, 66.0, 66.5, 67.0, 67.5, 68.0, 68.5, 69.0, 69.5 or 70.0), but are not limited to the listed values, other values not listed within the numerical range are also applicable.
[0033] In some optional examples, the mass fraction of the resin solution is 40 wt.%.
[0034] In a second aspect, the present invention provides an anti-rust coating composition prepared by the preparation method described in the first aspect.
[0035] In a third aspect, the present invention provides an anti-rust coating composition for use in high-temperature pipelines / pipelines.
[0036] Compared with the prior art, the present invention has the following beneficial effects: (1) Based on the composite of oxygen vacancy bismuth vanadate and zirconium phosphate, the electrochemical corrosion process is effectively inhibited and thermal stress shock is buffered. The active phosphate groups immobilized on the surface migrate to the damaged area at high temperature and react with the exposed substrate to form a dense passivation film, thereby achieving immediate self-sealing of microcracks. The rigid-flexible interpenetrating network formed by phosphazene chloride and tungstosilicoic acid, the released tungsten oxide anions are deposited at the crack tip to form a chemical sealing layer, giving the coating dynamic self-healing ability; (2) Aluminum magnesium molybdenum phosphate glass ceramics construct ion selective channels through controlled phase separation, lithium ions and molybdate synergistically intercept the penetration of corrosive media, strengthen the coating interface bonding, the rigid conjugated skeleton of biphenyl polyaryletherketone resin resists high-temperature segment dissociation, and the fluorosilane end group is doubly anchored to the metal substrate through covalent bonds and electrostatic adsorption, achieving excellent protection effect. DETAILED DESCRIPTION
[0037] The technical solutions of the present invention are described in detail below with reference to specific embodiments. The embodiments described herein are specific embodiments of the present invention and are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be understood as limiting the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments described herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments described herein.
[0038] The chemical reagents used in the examples and comparative examples of the present invention are all commercially available products and have not been subjected to any further purification treatment.
[0039] Example 1 This embodiment provides an anti-rust coating composition and a preparation method thereof, wherein the preparation method specifically comprises the following steps: A1, dispersing 4.8g of bismuth nitrate pentahydrate in 30g of 4M nitric acid solution to obtain a bismuth solution, dispersing 1.1g of ammonium metavanadate in 25g of 2M sodium hydroxide solution and adding the solution to the bismuth solution, adjusting the pH to 2.0, transferring the mixture to a polytetrafluoroethylene-lined reactor for a hydrothermal reaction at a temperature of 180°C for 12h, and drying to obtain BiVO4, placing the BiVO4 in a tube furnace, introducing a mixed gas, wherein the mixed gas is an H2 / Ar mixed gas with a hydrogen volume fraction of 5% at a total flow rate of 50mL / min, heating to 400°C and holding for 2h to obtain BiVO4-δ, mixing 10g of α-zirconium phosphate with 10g of BiVO4-δ, ball milling the mixture, immersing the mixture in a 0.1M sodium dihydrogen phosphate solution, filtering, washing, and drying to obtain a BiVO4 composite material; A2, dispersing 10g of silicotungstic acid in 50mL of anhydrous ethanol to obtain a silicotungstic acid ethanol solution, dispersing 5g of chlorophosphazene polymer in 50mL of anhydrous ethanol and adding the silicotungstic acid ethanol solution to stir evenly, filtering, washing, and drying to obtain a chlorophosphazene polymer composite; A3, 50 g of aluminum dihydrogen phosphate, 30 g of basic magnesium carbonate, and 15 g of lithium molybdate were mixed and ball-milled, and then 8 g of ammonium dihydrogen phosphate was added and allowed to stand and mature for 12 h to obtain a mixture. The mixture was heated to 1300°C and maintained for 1.5 h. The melt was poured into ice water and the fragments were immersed in 5 wt.% ammonia water. The mixture was ball-milled and dried to obtain a glass ceramic; S1, 100 g of 4,4'-difluorobenzophenone and 60 g of 4,4'-biphenol were dispersed in 600 g of sulfolane and 70 g of potassium carbonate was added. The mixture was heated to 190° C. under a nitrogen atmosphere and reacted for 3 h. The temperature was then lowered to 150° C. and 5 g of pentafluorophenyltriethoxysilane was added and the reaction was continued for 2 h. The reaction solution was cooled to room temperature and poured into ice water to obtain a precipitate. The precipitate was crushed, washed, and dried to obtain a modified resin. The modified resin was dispersed in N-methylpyrrolidone to obtain a resin solution. S2, 8g of BiVO4 composite material, 5g of chlorophosphazene polymer composite, 10g of glass ceramic and 1g of phosphate coupling agent are dispersed in 20g of N-methylpyrrolidone, and after ultrasonic dispersion, 65g of 40wt.% resin solution is added, and the mixture is ground on a three-roll mill to obtain an anti-rust coating composition.
[0040] Example 2 This embodiment provides an anti-rust coating composition and a preparation method thereof, wherein the preparation method specifically comprises the following steps: A1, 5.0g of bismuth nitrate pentahydrate was dispersed in 30g of 4M nitric acid solution to obtain a bismuth solution, 1.15g of ammonium metavanadate was dispersed in 25g of 2M sodium hydroxide solution and added to the bismuth solution, and the pH was adjusted to 2.2. The mixture was transferred to a polytetrafluoroethylene-lined reactor for hydrothermal reaction at a temperature of 182°C for 12.3h. After drying, BiVO4 was obtained. The BiVO4 was placed in a tube furnace and introduced with a mixed gas, wherein the mixed gas was an H2 / Ar mixed gas with a hydrogen volume fraction of 5% and a total flow rate of 50mL / min. The temperature was raised to 410°C and maintained for 3h to obtain BiVO4-δ. 10g of α-zirconium phosphate was mixed with 10g of BiVO4-δ, ball-milled, immersed in a 0.1M sodium dihydrogen phosphate solution, filtered, washed, and dried to obtain a BiVO4 composite material; A2, dispersing 10.5 g of silicotungstic acid in 50 mL of anhydrous ethanol to obtain a silicotungstic acid ethanol solution, dispersing 5 g of chlorophosphazene polymer in 50 mL of anhydrous ethanol and adding the silicotungstic acid ethanol solution to stir evenly, filtering, washing, and drying to obtain a chlorophosphazene polymer composite; A3, 55 g of aluminum dihydrogen phosphate, 35 g of basic magnesium carbonate, and 15 g of lithium molybdate were mixed and ball-milled, and then 10 g of ammonium dihydrogen phosphate was added and allowed to stand and mature for 13 h to obtain a mixture. The mixture was heated to 1310°C and maintained for 2.0 h. The melt was poured into ice water and the fragments were immersed in 5 wt.% ammonia water. The mixture was ball-milled and dried to obtain a glass ceramic; S1, 115g of 4,4'-difluorobenzophenone and 65g of 4,4'-biphenyldiphenol were dispersed in 600g of sulfolane and 70g of potassium carbonate was added. The mixture was heated to 192°C under a nitrogen atmosphere and reacted for 4h. The temperature was then lowered to 152°C and 5g of pentafluorophenyltriethoxysilane was added and the reaction was continued for 3h. The reaction solution was cooled to room temperature and poured into ice water to obtain a precipitate. The precipitate was crushed, washed, and dried to obtain a modified resin. The modified resin was dispersed in N-methylpyrrolidone to obtain a resin solution. S2, 9g of BiVO4 composite material, 7g of chlorophosphazene polymer composite, 13g of glass ceramic and 1g of phosphate coupling agent are dispersed in 20g of N-methylpyrrolidone, and after ultrasonic dispersion, 70g of 40wt.% resin solution is added, and the mixture is ground on a three-roll mill to obtain an anti-rust coating composition.
[0041] Example 3 This embodiment provides an anti-rust coating composition and a preparation method thereof, wherein the preparation method specifically comprises the following steps: A1, dispersing 4.9g of bismuth nitrate pentahydrate in 30g of 4M nitric acid solution to obtain a bismuth solution, dispersing 1.2g of ammonium metavanadate in 25g of 2M sodium hydroxide solution and adding the solution to the bismuth solution, adjusting the pH to 2.5, transferring the solution to a polytetrafluoroethylene-lined reactor for a hydrothermal reaction at a temperature of 185°C for 13h, and drying the solution to obtain BiVO4. The BiVO4 was placed in a tube furnace and introduced with a mixed gas, wherein the mixed gas was an H2 / Ar mixed gas with a hydrogen volume fraction of 5% and a total flow rate of 50mL / min. The temperature was raised to 420°C and maintained for 2.4h to obtain BiVO4-δ. 10g of α-zirconium phosphate was mixed with 10g of BiVO4-δ, ball-milled, immersed in a 0.1M sodium dihydrogen phosphate solution, filtered, washed, and dried to obtain a BiVO4 composite material. A2, dispersing 10.2 g of silicotungstic acid in 50 mL of anhydrous ethanol to obtain a silicotungstic acid ethanol solution, dispersing 5 g of chlorophosphazene polymer in 50 mL of anhydrous ethanol and adding the silicotungstic acid ethanol solution to stir evenly, filtering, washing, and drying to obtain a chlorophosphazene polymer composite; A3, 51 g of aluminum dihydrogen phosphate, 31 g of basic magnesium carbonate, and 15 g of lithium molybdate were mixed and ball-milled, and then 9 g of ammonium dihydrogen phosphate was added and allowed to stand and mature for 12.4 h to obtain a mixture. The mixture was heated to 1320°C and maintained at this temperature for 1.7 h. The melt was poured into ice water, and the fragments were immersed in 5 wt.% ammonia water. The mixture was ball-milled and dried to obtain a glass-ceramic. S1, 110g of 4,4'-difluorobenzophenone and 61g of 4,4'-biphenyldiphenol were dispersed in 600g of sulfolane and 70g of potassium carbonate was added. Under nitrogen atmosphere, the temperature was raised to 195°C and the reaction was continued for 3.3h. The temperature was then lowered to 155°C and 5g of pentafluorophenyltriethoxysilane was added and the reaction was continued for 2.4h. The reaction solution was cooled to room temperature and poured into ice water to obtain a precipitate. The precipitate was crushed, washed and dried to obtain a modified resin. The modified resin was dispersed in N-methylpyrrolidone to obtain a resin solution; S2, 10g of BiVO4 composite material, 6g of chlorophosphazene polymer composite, 12g of glass ceramic and 1g of phosphate coupling agent are dispersed in 20g of N-methylpyrrolidone, and after ultrasonic dispersion, 67g of 40wt.% resin solution is added, and the mixture is ground on a three-roll mill to obtain an anti-rust coating composition.
[0042] Example 4 This embodiment provides an anti-rust coating composition and a preparation method thereof, wherein the preparation method specifically comprises the following steps: A1, 5.0g of bismuth nitrate pentahydrate was dispersed in 30g of 4M nitric acid solution to obtain a bismuth solution, 1.18g of ammonium metavanadate was dispersed in 25g of 2M sodium hydroxide solution and added to the bismuth solution, and the pH was adjusted to 2.3. The mixture was transferred to a polytetrafluoroethylene-lined reactor for hydrothermal reaction at a temperature of 184°C and a time of 12.7h. After drying, BiVO4 was obtained. The BiVO4 was placed in a tube furnace and introduced with a mixed gas, wherein the mixed gas was an H2 / Ar mixed gas with a hydrogen volume fraction of 5% and a total flow rate of 50mL / min. The temperature was raised to 415°C and maintained for 2.8h to obtain BiVO4-δ. 10g of α-zirconium phosphate was mixed with 10g of BiVO4-δ, ball-milled, immersed in a 0.1M sodium dihydrogen phosphate solution, filtered, washed, and dried to obtain a BiVO4 composite material; A2, dispersing 10.4 g of silicotungstic acid in 50 mL of anhydrous ethanol to obtain a silicotungstic acid ethanol solution, dispersing 5 g of chlorophosphazene polymer in 50 mL of anhydrous ethanol and adding the silicotungstic acid ethanol solution to stir evenly, filtering, washing, and drying to obtain a chlorophosphazene polymer composite; A3, 54 g of aluminum dihydrogen phosphate, 33 g of basic magnesium carbonate, and 15 g of lithium molybdate were mixed and ball-milled, and then 8.5 g of ammonium dihydrogen phosphate was added and allowed to stand and mature for 12.8 h to obtain a mixture. The mixture was heated to 1315°C and maintained for 1.9 h. The melt was poured into ice water, and the fragments were immersed in 5 wt.% ammonia water, and ball-milled and dried to obtain a glass ceramic; S1, 108g of 4,4'-difluorobenzophenone and 64g of 4,4'-biphenyldiphenol were dispersed in 600g of sulfolane and 70g of potassium carbonate was added. Under nitrogen atmosphere, the temperature was raised to 194°C and the reaction was continued for 3.6h. The temperature was then lowered to 154°C and 5g of pentafluorophenyltriethoxysilane was added and the reaction was continued for 2.7h. The reaction solution was cooled to room temperature and poured into ice water to obtain a precipitate. The precipitate was crushed, washed and dried to obtain a modified resin. The modified resin was dispersed in N-methylpyrrolidone to obtain a resin solution; S2, 8.5g of BiVO4 composite material, 5.5g of chlorophosphazene polymer composite, 11g of glass ceramic and 1g of phosphate coupling agent were dispersed in 20g of N-methylpyrrolidone, and after ultrasonic dispersion, 69g of 40wt.% resin solution was added, and the mixture was ground on a three-roll mill to obtain an anti-rust coating composition.
[0043] Comparative Example 1 This comparative example provides an anti-rust coating composition and a preparation method thereof. The difference between the comparative example and Example 1 is that the mass of the BiVO4 composite material in S2 is 0, and the other process parameters and operating conditions are exactly the same as those in Example 1.
[0044] Comparative Example 2 This comparative example provides an anti-rust coating composition and a preparation method thereof. The difference between the comparative example and Example 1 is that the mass of the chlorophosphazene polymer composite in S2 is 0, and the other process parameters and operating conditions are exactly the same as those in Example 1.
[0045] Comparative Example 3 This comparative example provides an anti-rust coating composition and a preparation method thereof, which differs from Example 1 in that the mass of the glass ceramic in S2 is 0, and other process parameters and operating conditions are exactly the same as those in Example 1.
[0046] High-temperature adhesion test method: A low-carbon steel plate (100*100*25mm) was used as the substrate. After the coating was cured, a high-temperature tensile testing machine was used. The specimen was mounted in the test chamber and heated to the target temperature (200°C) at a rate of 5°C / min. The temperature was maintained constant for 30 minutes to ensure temperature uniformity. A tensile load was applied at a constant rate of 1 MPa / s until the coating peeled off. The maximum load value was recorded in real time.
[0047] Thermal shock test method: The specimen size is 50*50*3mm, with the edge chamfered by 0.5mm. Place it in a muffle furnace preheated to 200℃ and keep it warm for 15 minutes. Then quickly transfer it to a 25℃ deionized water bath (transfer time ≤ 10 seconds). After soaking for 10 seconds, take it out and blow it dry. After each cycle, inspect the coating surface with the naked eye under oblique white light. If continuous linear lines are found, it is considered unqualified. Suspicious areas are re-inspected with a 20x handheld microscope to confirm the crack morphology. Repeat the cycle until visible cracks appear or 15 cycles are completed.
[0048] High temperature oxidation-salt spray coupling test method: Take a 304 stainless steel substrate (100*100*3mm), sandblast it to a surface roughness of Sa2.5, chamfer the edge with 0.5mm, control the dry film thickness to 50±5μm, and cover the edge with high temperature resistant silicone sealant with an exposed area of 80cm². After the sample is dried at 120℃ for 1 hour, the initial mass m0 is recorded, and the sample is fixed on the salt spray chamber sample rack with an angle of 15°. The temperature in the chamber is maintained at 35℃±1℃, and the spray mass fraction is 5%. A sodium chloride solution (compliant with ASTM B117) was sprayed for 4 hours to ensure a salt deposition of 3.5 ± 0.5 mg / cm² (three specimens per batch were randomly sampled and weighed for verification). After spraying, the specimens were placed in a 60°C forced air drying oven and allowed to stand for 1 hour to form a uniform salt film. The muffle furnace was preheated to 200°C ± 10°C. Within 10 seconds of opening the furnace door, the specimens were transferred to the center of the furnace chamber and held in an air atmosphere for 2 hours, with the furnace temperature fluctuation controlled within ±5°C. After the holding period, the specimens were immediately placed on a forced air cooling platform. The salt spray and high-temperature oxidation process was repeated for a total of 20 cycles. The sealant integrity was inspected and any damage was immediately re-coated. Corrosion weight gain was determined: the specimens were ultrasonically cleaned with deionized water, dried, and the final mass, m1, was weighed. The mass change per unit area was calculated as: corrosion weight gain = (m1 - m0) / 80. The test was terminated if any of the following conditions occurred: visible coating delamination or cracks were observed in cross-sections extending to the substrate interface.
[0049] The test results are shown in Table 1.
[0050] Table 1 Test results of an anti-rust coating composition of Examples 1 to 4 and Comparative Examples 1 to 3
[0051] As shown in Table 1, compared with Example 1, the high-temperature adhesion of Comparative Example 1 decreased, the thermal shock test effect decreased, and the corrosion weight gain increased; the high-temperature adhesion of Comparative Example 2 decreased, the thermal shock test effect decreased, and the corrosion weight gain increased; the high-temperature adhesion of Comparative Example 3 decreased, the thermal shock test effect decreased, and the corrosion weight gain increased. This is because the mass of the BiVO4 composite material in Comparative Example 1 is 0, the lack of oxygen vacancy electron traps, the substrate anode dissolution is aggravated, and the self-repair function fails. The thermal stress cracks cannot be closed by the iron phosphate passivation film, so the high-temperature protection effect decreases. The mass of the chlorophosphazene polymer composite in Comparative Example 2 is 0, the stress dissipation network disappears, the thermal expansion stress is concentrated at the interface, the brittleness of the coating increases, the microcracks become corrosion channels, and the corrosion weight gain increases. The mass of the glass ceramic in Comparative Example 3 is 0, and it is impossible to construct a negative charge barrier on the surface of the metal substrate by chemical adsorption to repel corrosive media such as chloride ions.
[0052] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing an anti-rust coating composition, characterized in that: The preparation method comprises: A1, dispersing bismuth nitrate pentahydrate in a nitric acid solution to obtain a bismuth solution, dispersing ammonium metavanadate in a sodium hydroxide solution and adding the solution to the bismuth solution for a hydrothermal reaction to obtain BiVO4, placing the BiVO4 in a tube furnace and introducing a mixed gas to maintain the temperature to obtain BiVO4-δ, mixing α-zirconium phosphate and BiVO4-δ, ball-milling the mixture, immersing the mixture in a sodium dihydrogen phosphate solution, filtering, washing, and drying to obtain a BiVO4 composite material; S1, dispersing 4,4'-difluorobenzophenone and 4,4'-biphenol in sulfolane and adding potassium carbonate to react, adding pentafluorophenyltriethoxysilane to continue the reaction to obtain a modified resin, and dispersing the modified resin in N-methylpyrrolidone to obtain a resin solution; S2, dispersing the BiVO4 composite material, the chlorophosphazene polymer composite, the glass ceramic and the phosphate coupling agent in N-methylpyrrolidone, adding the resin solution after ultrasonic dispersion, and obtaining an anti-rust coating composition.
2. The method for preparing an anti-rust coating composition according to claim 1, wherein: The preparation method of the chlorophosphazene polymer composite comprises: A2, dispersing silicotungstic acid in anhydrous ethanol to obtain a silicotungstic acid ethanol solution, dispersing a chlorophosphazene polymer in anhydrous ethanol and adding the silicotungstic acid ethanol solution to stir evenly, filtering, washing, and drying to obtain a chlorophosphazene polymer composite.
3. The method for preparing an anti-rust coating composition according to claim 1, characterized in that: The preparation method of the glass ceramic comprises: A3, aluminum dihydrogen phosphate, basic magnesium carbonate and lithium molybdate are mixed and ball-milled, and then ammonium dihydrogen phosphate is added and allowed to stand and mature to obtain a mixture, the mixture is heated to obtain a melt, the melt is poured into ice water, and the fragments are immersed in ammonia water, and ball-milled and dried to obtain glass ceramics.
4. The method for preparing an anti-rust coating composition according to claim 1, wherein: In A1: The mass ratio of the bismuth nitrate pentahydrate to ammonium metavanadate is (4.8-5.0): (1.1-1.2); The mixed gas is H2 / Ar mixed gas, the volume fraction of hydrogen is 5%, and the total flow rate is 50 mL / min; The mass ratio of the α-zirconium phosphate to BiVO4-δ is 1:
1.
5. The method for preparing an anti-rust coating composition according to claim 1, characterized in that: In S1: The mass ratio of the 4,4'-difluorobenzophenone, 4,4'-biphenol, sulfolane, potassium carbonate and pentafluorophenyltriethoxysilane is (100-115): (60-65): 600: 70:
5.
6. The method for preparing an anti-rust coating composition according to claim 1, characterized in that: In S2: The mass ratio of the BiVO4 composite material, the chlorophosphazene polymer composite, the glass ceramic, the phosphate coupling agent, the N-methylpyrrolidone and the resin solution is (8-10): (5-7): (10-13): 1:20: (65-70); The mass fraction of the resin solution is 40 wt.%.
7. The method for preparing an anti-rust coating composition according to claim 2, characterized in that: In A2: The mass ratio of the silicotungstic acid to the chlorophosphazene polymer is (2-2.1):
1.
8. The method for preparing an anti-rust coating composition according to claim 3, characterized in that: In A3: The mass ratio of the aluminum dihydrogen phosphate, basic magnesium carbonate, lithium molybdate and ammonium dihydrogen phosphate is (50-55): (30-35): 15: (8-10).
9. An anti-rust coating composition obtained according to the preparation method according to any one of claims 1 to 8.
10. Use of an anti-rust coating composition obtained according to the preparation method according to any one of claims 1 to 8 in high-temperature pipelines / pipelines.
Citation Information
Patent Citations
Coated metal sheet for automobile excellent in rust resistance in low temperature running environments
US20170298231A1
Cited By
High-adhesion nanometer silicon coating and preparation method thereof
CN121801398A